Factores asociados con la adherencia a la actividad física en el tiempo libre (2014)
ABSTRACT: In Colombia there is a low knowledge related to the associated factors with adherence to exercise. Objective: To evaluate the associated factors with adherence to the physical activity in leisure time in adults (PALT) who participate in a physical activity program. Methods: The study was a prospective case-control. A case was defined as who performed during five months an average of 150 minutes or more per week of PALT, with a moderate intensity or strong intensity of 75 minutes or more of PALT per week; as a control was had in consideration, people who did not meet the above criteria. The independent variables measured were: sociodemographic factors, cardiovascular, musculoskeletal risk factors, and the motivation to exercise. The data was analyzed through a varied regressive logistic model. Results: The sample involved 176 female users of a PA program (69.3%); with an average age of 55.7 years old. The associated variables with the PALT adherence were the personal osteoarthritis record (OR 0,392; IC95% 0,184 – 0,837; P=0,016) and the age (OR 1,027; IC95% 1,001-1,054; p=0,041), which explained 8, 0 % of the variability. Conclusions: The variables that were independently associated to the adherence to PALT were age, and the personal osteoarthritis record. There is a necessity of new studies that include new variables to allow a global analysis of the phenomena.